An embarrassment of riches : rekindling desire for obsolete furniture : a exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Neale, Wendy (Massey University, 2010)
This exegesis tells the story of my Master of Design project, Embarrassment of Riches. During this project I have gleaned obsolete furniture pieces and operated on them to present new possibilities. This text discusses the body of work I have created in the context of three main ideas: the use of gleaning, intervention and the role played by memory in rekindling desire. I have focussed on making in a heuristic, research-through-design practice, testing ideas through making/reflecting and then developing my ideas further in new pieces. Combining this actionresearch method with bricolage has enabled me to critically self-reflect on my practice. Through this I have discovered that I can continue to design and create objects in an age of overproduction and consumption. With ecological considerations in mind I can make obsolete objects desirable (again) by encouraging people to feel intimate with them. I intervene in the objects’ interstices to suggest histories that kindle engagement and attachment. The interstice has been a rich source of inspiration, not only as site of intervention, but as site where experimentation occurs, a process by which objects are found and a space where new genres develop.
Keywords: Recycled furniture; Design; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410204 Crafts studies